2008
DOI: 10.1149/1.2919561
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Phase Composition and Luminescence of Sr[sub 6]BP[sub 5]O[sub 20] on Eu Concentration

Abstract: We have investigated how secondary phases appear and disappear upon increasing europium concentration from 1.5 to 16.2 atom % in standard strontium borophosphate phosphate phosphor, Sr 6 BP 5 O 20 , using X-ray diffraction and photoluminescence and photoluminescence excitation measurements both at room temperature and at 80 K. In standard phosphor, a minor phase of strontium phosphate, Sr 3 ͑PO 4 ͒ 2 , was detected besides the main component Sr 6 BP 5 O 20 . With increasing Eu concentration, the phase Sr 3 ͑PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…First, the electrons are available from the matrix or synthetic atmosphere to enable the reduction from Eu 3+ to Eu 2+ ; second, the matrix should have a capability to offer a stable lattice environment for the Eu 2+ . Therefore it is considered that the special structure [ ] tetrahedral unit in silicate glasses, and form three-dimensional network which plays an important role in the stability of rare earth ions [13,14] . When the ratio of B/P exceeds 1.4, however, the glass structure tends to deviate from the suitable structure, resulting in a decrease in the intensity of blue emission.…”
Section: Fig1 Pl Spectra Of the Glass Samples With Different Glass Cmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the electrons are available from the matrix or synthetic atmosphere to enable the reduction from Eu 3+ to Eu 2+ ; second, the matrix should have a capability to offer a stable lattice environment for the Eu 2+ . Therefore it is considered that the special structure [ ] tetrahedral unit in silicate glasses, and form three-dimensional network which plays an important role in the stability of rare earth ions [13,14] . When the ratio of B/P exceeds 1.4, however, the glass structure tends to deviate from the suitable structure, resulting in a decrease in the intensity of blue emission.…”
Section: Fig1 Pl Spectra Of the Glass Samples With Different Glass Cmentioning
confidence: 99%
“…As to where the Eu ions exist in the multiphase and multi-component system of borophosphate glass ceramics, we propose that the Eu ions in the glass-ceramics can exist in the sites of the glassy phase, the sites inside the nanocrystals and the sites localized at the interface between the crystal particles and the glassy phase [13][14][15][16][17] . With the amount of B 2 O 3 increases, the amount of Sr(PO 3 ) 2 crystal increases, which indicates the increase of Eu 2+ to substitute the more sites of Sr 2+ in the crystalline phase to intensify the blue emission.…”
Section: Fig4 Pl Spectra Of Blue-light and Red-light Borophosphate Gmentioning
confidence: 99%
“…For example, EuCaAl 3 O 7 appears as a secondary phase at above 6 mol % of the Eu 2+ concentration in the CaAl 2 O 4 :Eu 2+ phosphor synthesis using Eu 2 O 3 even in a reducing atmosphere. 14 Laubach et al 15 also reported that Sr 3 Eu͑PO 4 ͒ 3 , as well as SrBPO 5 and Sr 2 P 2 O 7 , are formed as a secondary phase at above 2 mol % of the Eu 2+ concentration in the Sr 6 BP 5 O 20 :Eu 2+ phosphor synthesis using Eu 2 O 3 . These reports suggest that the influence of the increased oxygen content by using Eu 2 O 3 on the phosphor synthesis cannot be negligible at the high Eu concentration range.…”
mentioning
confidence: 97%